Pengaruh Penambahan Konsentrasi Pasir Besi dalam Resin Epoksi pada Sifat Korosi Besi Karbon: Linda Silvia, Mochamad Zainuri - Linda Silvia, Linda Silvia; Mochamad Zainuri, Mochamad Zainuri (Jurnal Fisika dan Aplikasinya, 2025)
The effect of adding iron sand concentration in epoxy resin on the corrosion rate of carbon steel had been studied with mass loss method measurement. In this research work, iron sand was separated by magnet and iron sand/epoxy composites coating applied to carbon steel. Experiments was carried out by controlling concentration of iron sand with variation in composition 0%wt, 10%wt, 30%wt, and 50%wt of the weight composites total, and then carbon steel was immersion at NaCl 10 M and drying at room temperature. The composite has been formed is immersed into a solution of 10 M NaCl for 21 days and then tested the corrosion rate. The composites were characterized using X-Ray Diffractometer (XRD) for phase identification of iron sand and X-ray fluorescence (XRF) for measure composition of elements and oxides of iron sand. Corrosion rate of composite materials was indentified with mass loss method. The results showed that analysis of the corrosion rate measurements obtained the largest mass loss of corrosion rate occur in concentrations addition of 30%wt of the weight composites total was 71.9246 mpy and the corrosion rate of decline occurred in 50%wt of the weight composites total was 12.5379 mpy, which has good corrosion resistance that can be used as a coating of ships paint.